Student’s Satisfaction of Learning in Body Fitness Course - Jin, Xueyu; Niyomsilp, Eksiri (Journal of Modern Learning Development, 2023)
College students are the main body of college physical education courses. Their satisfaction can reflect the quality of university fitness and bodybuilding courses to a certain extent. To this end, this study borrows the theoretical model of customer satisfaction, adopts a hybrid research method, and builds a model satisfaction model of college students' fitness and bodybuilding courses through in-depth interviews, then verify the assumption proposed by the model. The study found:1. Teacher image has a positive impact on student expectation, Perceived quality, and student satisfaction; Students expect a significant positive impact on perceived value; Perceived quality has a positive and positive impact on perception value and student satisfaction. The study also found: Perceived quality and perceived value plays a part of the intermediary role in the path that the teacher image affects students' satisfaction; Student expectation and perceived values play a part of the intermediary role in the path of teacher's satisfaction.